Management of Septic Arthritis of the Temporomandibular Joint in Dogs - Arzi, Boaz; Vapniarsky, Natalia; Fulton, Amy; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2021)
Septic arthritis of the temporomandibular joint (TMJ) in dogs and other mammals is a rare condition. It is typically associated with notable pain, swelling and difficulty in opening the mouth. Unlike degenerative TMJ disease, septic arthritis requires urgent intervention. The condition's etiology may include penetrating trauma, an extension of a local infection such as otitis media, or hematogenous spread of a pathogen. However, the precise cause may not always be identified. Diagnostic imaging by means of computed tomography (CT), cone-beam CT (CBCT) and/or magnetic resonance imaging (MRI) are helpful at honing in on the definitive diagnosis and formulating a treatment plan. Subsequently, exploratory surgery to obtain samples for culture and sensitivity, and histology, and to lavage the joint may be required. In this ‘methods’ article, we provide a detailed description of our approach to diagnosis and management of septic TMJ arthritis in four dogs.